Research companion to green international management studies : a guide for future research, collaboration and review writing - De Lange, Deborah E. (Cheltenham : Edward Elgar, 2010)
Comprehensively covers the field of sustainability and the environment in business and management -- Back cover.
Includes bibliographical references and index.
Keywords: Social responsibility of business; Business enterprises -- Environmental aspects; Environmental responsibility